2016
DOI: 10.1371/journal.pone.0155685
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium massiliense Induces Macrophage Extracellular Traps with Facilitating Bacterial Growth

Abstract: Human neutrophils have been known to release neutrophil extracellular traps (NETs), antimicrobial DNA structures capable of capturing and killing microbes. Recently, a similar phenomenon has been reported in macrophages infected with various pathogens. However, a role for macrophages extracellular traps (METs) in host defense responses against Mycobacterium massiliense (M. mass) has yet to be described. In this study, we show that M. mass, a rapid growing mycobacterium (RGM), also induces the release of METs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 59 publications
3
33
2
1
Order By: Relevance
“…Shen et al [40] found similar results with AAPVtreated mouse peritoneal macrophages infected with S. aureus. In contrast, Je et al [26] noted AAPV-treated THP-1 macrophage-like cells infected with M. massili ense were unaffected with regard to MET release despite elastase being identified within the MET structures. Muñoz-Caro et al [23] inhibited MET release by bovine monocytes infected with Besnoitia besnotii trachyzoites using the MPO inhibitor, 4-aminobenzoic acid hydrazide (ABAH).…”
Section: Cellular Pathways Implicated In Met Releasementioning
confidence: 88%
See 4 more Smart Citations
“…Shen et al [40] found similar results with AAPVtreated mouse peritoneal macrophages infected with S. aureus. In contrast, Je et al [26] noted AAPV-treated THP-1 macrophage-like cells infected with M. massili ense were unaffected with regard to MET release despite elastase being identified within the MET structures. Muñoz-Caro et al [23] inhibited MET release by bovine monocytes infected with Besnoitia besnotii trachyzoites using the MPO inhibitor, 4-aminobenzoic acid hydrazide (ABAH).…”
Section: Cellular Pathways Implicated In Met Releasementioning
confidence: 88%
“…Additional verification that proposed structures are ETs can be obtained by staining for known ET components such as histones, elastase, or MPO. Elastase, often considered a neutrophil-specific marker, has been identified in the METs of human peripheral-blood monocytes and in THP-1 macrophage-like cells [22,26]. Similarly, MPO has been identified in the METs of diverse macrophage populations including human glomerular macrophages, human peripheral-blood monocytes, THP-1 macrophage-like cells, murine J774A.1 macrophage-like cells, bovine monocytes, and caprine monocytes [22,23,[26][27][28][29] (Table 1).…”
Section: Defining and Identifying Metsmentioning
confidence: 99%
See 3 more Smart Citations